Venous thromboembolism in pregnant and puerperal women in Denmark 1995–2005 - Virkus, Rie Adser; Løkkegaard, Ellen Christine Leth; Bergholt, Thomas; Mogensen, Ulla; Langhoff-Roos, Jens; Lidegaard, øjvind (Thrombosis and Haemostasis, 2011)
Venous thromboembolism (VTE) is the leading cause of maternal death in the Western world, and the risk increases during pregnancy and puerperal period. It was the objective of the present study to estimate the absolute and the relative risk of VTE at different weeks of gestation and in the postnatal period as compared to non-pregnant women. This was a historical controlled national cohort study. The National Registry of Patients identified relevant diagnoses. These data were linked to The National Registry of Medical Products Statistics for information about current use of oral contraceptives. Danish women 15 to 49 years old during the period January 1995 through December 2005 were included in the study. In total 819,751 pregnant women were identified of whom 727 had a diagnosis of VTE. The absolute risk of VTE per 10,000 pregnancy-years increased from 4.1 (95% CI, 3.2 to 5.2) during week 1–11 up to 59.0 (95% CI: 46.1 to 76.4) in week 40 and decreased in the puerperal period from 60.0 (95% CI:47.2–76.4) during the first week after birth to 2.1 (95% CI:1.1 to 4.2) during week 9–12 after birth. Compared with non-pregnant women, the incidence rate ratio rose from 1.5 (95% CI:1.1 to1.9) in week 1–11, to 21.0 (95%CI16.7 to 27.4) in week 40 and 21.5 (95% CI:16.8 to 27.6) in the first week after delivery, declining to 3.8 (95% CI:2.5 to 5.8) 5–6 weeks after delivery. In conclusion, the risk of VTE increases almost exponentially through pregnancy and reaches maximum just after delivery and is no longer significantly increased six weeks after delivery.
Keywords: Venous thromboembolism; pregnancy; pulmonary embolism; deep venous thrombosis